HOSPITAL PHYSICAL THERAPY MANAGEMENT IN PEDIATRIC PATIENTS WITH COVID-19: CASE REPORTS - Camila Wohlgemuth Schaan; Vanessa de Souza Vieira; Cristina Miller; Ana Paula Dattein Peiter; Taciana Piccoli; Gabriela Cavion; Janice Luisa Lukrafka; Renata Salatti Ferrari (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To report the physiotherapeutic management of two pediatric cases with COVID-19 admitted in a reference state hospital to treat the disease in Porto Alegre, Southern Brazil. Cases description: Case 1, female, 10-month-old child, pre-existing chronic disease, hospitalized since birth, mechanical ventilation dependency via tracheotomy, progressed with hypoxemia, requiring oxygen therapy, and increased ventilator parameters, and a diagnosis of COVID-19 was confirmed. Airway clearance and pulmonary expansion maintenance therapies were performed. During hospitalization, the child acquired cephalic control, sitting without support, rolling, holding, and reaching objects. Recommendations were provided to a family member to maintain motor development milestones. Case 2, male, nine years old, previous psychiatric disease and obesity, showed worsening of the sensory state, requiring intensive care and invasive mechanical ventilation, with the diagnosis of SARS-Cov-2 infection. The physical therapy was performed to maintain airway clearance, pulmonary expansion, and early mobilization, showing ventilatory improvement during the intensive care hospitalization and successfully extubated after 17 days. The physical therapy evolved from passive to resistive exercises during the hospitalization, and the patient was able to walk without assistance at discharge, with the same previous functional status. Comments: The COVID-19 showed different manifestations in both cases. Physical therapy treatment was essential to maintain and to recover the functional status of the patients. Future studies are needed to improve the understanding of disease course and its functional consequences to offer an efficient treatment to pediatric patients with COVID-19.